Lysine degradation by ruminal Fusobacteriumnecrophorum - E.A. Elwakeel; R.G. Amachawadi; A.M. Nour; M.E. Nassar (Kansas Agricultural Experiment Station Research Reports, 2010)
Three experiments were conducted to characterize lysine fermentation by Fusobacterium necrophorum, a ruminal bacterium that is known to degrade amino acids. In Experiment 1, 7 strains of Fusobacterium necrophorum were inoculated into media containing lysine (50 mM), lactate (50 mM), or lysine plus lactate (50 mM each) as the major energy substrate to evaluate growth and ammonia production. All strains grew with lysine, lactate, or lactate plus lysine as the primary substrate. When grown with lysine, all strains produced ammonia as an end product, even if lactate was also present. Smaller concentrations of ammonia for medium containing lactate plus lysine when compared with lysine alone indicate that the Fusobacterium strains used lactate as a growth substrate that stimulated utilization of ammonia. In Experiment 2, the 2 strains tested were able to degrade extensively both lysine and glutamic acid. Some evidence was detected for partial utilization for growth of histidine, methionine, and tryptophan by strain A21. In Experiment 3, the minimum inhibitory concentration (MIC) of the antibiotic tylosin was 25 Î¼g/mL when Fusobacterium necrophorum strains A21 and B35 were grown in either lysine or lactate-enriched medium. The MIC of monensin was 6.25 and 3.9 Î¼g/mL for strains A21 and B35, respectively, when grown in lysine-enriched medium, but>50 and 10.9 Î¼g/mL when the strains were grown in lactate-enriched medium. These findings may lead to ways that ruminal lysine degradation may be controlled.; Dairy Day, 2010, Kansas State University, Manhattan, KS, 2010; Dairy Research, 2010 is known as Dairy Day, 2010
Keywords: Dairy Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-129-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1039; Dairy; Bacterial digestion; Lactate; Lysine degradation